2018
DOI: 10.1101/266783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mavacamten stabilizes a folded-back sequestered super-relaxed state of β-cardiac myosin

Abstract: Abstract:Mutations in β-cardiac myosin, the predominant motor protein for human heart contraction, can alter power output and cause cardiomyopathy. Previous studies suggest that myosin function can be regulated by entering a super-relaxed state (SRX) with very slow ATP hydrolysis, but the structural determinants of this state are uncertain. Using a combination of biochemical approaches with electron microscopy and X-ray fiber diffraction, we show that the SRX corresponds to a folded-back state of myosin with i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The small molecule drug candidate mavacamten has been found to decrease contractility and suppress the development of hypertrophy and fibrosis in HCM mouse models [ 83 ]. Mavacamten appears to reduce the basal release rates of ADP and Pi [ 84 ], by stabilizing the myosin heads in an SRX state [ 23 ], similarly to blebbistatin. In support of this notion, we have shown that mavacampten significantly increases the myosin layer line intensities in relaxed skinned porcine cardiac muscle [ 23 ], consistent with an enrichment of the quasi-helically ordered SRX state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small molecule drug candidate mavacamten has been found to decrease contractility and suppress the development of hypertrophy and fibrosis in HCM mouse models [ 83 ]. Mavacamten appears to reduce the basal release rates of ADP and Pi [ 84 ], by stabilizing the myosin heads in an SRX state [ 23 ], similarly to blebbistatin. In support of this notion, we have shown that mavacampten significantly increases the myosin layer line intensities in relaxed skinned porcine cardiac muscle [ 23 ], consistent with an enrichment of the quasi-helically ordered SRX state.…”
Section: Discussionmentioning
confidence: 99%
“…The SRX state has been characterized as a state where myosin has a much lower ATPase rate than under normal conditions [ 20 ], explaining the low energy consumption in resting muscle. Structurally, myosin heads in the SRX state have been proposed to adopt the so-called interacting-head motif (IHM) where one of the two heads of a myosin molecule is folded back on to its own coiled-coil S2 tail [ 21 , 22 , 23 ]. In contrast, in the DRX state, myosin heads are presumed to be disordered and freely moving in the myofilament lattice with ATPase activity as high as with isolated myosin [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…While beyond the scope of this study, the assumption that the step size is unaffected could be tested using a single-molecule laser trap assay. Also, detailed direct biophysical measurements of the load dependence of the strongly-bound state are possible using Harmonic Force Spectroscopy (46) as well as measurements of the extent of sequestering of heads into a superrelaxed state (47). Furthermore, significant differences may be found using regulated thin filaments rather than purified actin in the ATPase measurements (14).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the IHM and the super-relaxed state have only been directly connected for the R403Q myosin mutation [ 112 ], but the weight of indirect evidence is compelling. The correlation of mutations with potential to destabilise the IHM seems solid for myosin heavy chain mutations and also for myosin light chain mutations and MyBP-C mutations causing haploinsufficiency.…”
Section: Unifying Hypothesis For Myosin and Mybp-c Mutations Causimentioning
confidence: 99%
“…It has been shown to be effective both in vitro and in vivo in reversing most of the basic symptoms of HCM [ 113 , 114 ]. A recent study has shown that the mode of action of Mavacampten is to stabilise the IHM structure and enhance the super-relaxed state of myosin [ 112 ].…”
Section: Unifying Hypothesis For Myosin and Mybp-c Mutations Causimentioning
confidence: 99%